La teoría de la prehistoria humana de Karl Marx - Boltvinik, Julio (El Colegio de México, 2021)
This article configures Marx’s theory of prehistory whose beginning (anthropogenesis) is marked by the manufacture of tools, making human work a vital activity designed to achieve the mediated satisfaction of needs, which turns humans into  beings that can convert the whole of  nature into the focus of their activity, universal beings. For this beginning, the article follows the philosophical anthropology of Marx-Markus. The end of prehistory becomes possible when human beings create the conditions to overcome scarcity and alienation. This is supported by a passage from Grundrisse that explains the objective limit of capitalism. Abundance and overcoming capitalism: prerequisites for the beginning of the history of the fully creative human being.